Public Relations Management in Building the Image of Schools in Senior High School - Hastomo Aji P; Dwi Esti Andriyani (AIBPM Publisher, 2020)
This study aims to explain the planning, implementation and evaluation of community relations to improve the image of schools. This case study research was conducted at a high school in one of the provinces in Indonesia with a qualitative method. This study findings reveal schools’ patterns of understanding of planning, organizing, implementing and evaluating to improve their collaborative relations with the surrounding community to improve schools’ quality through good internal and external cooperation. This study documents several key contributions made to establish a two-way, comprehensive communication in ensuring mutual cooperation on maintaining outstanding school quality assurance.